Impacto de la TIC`s en el proceso de enseñanza aprendizaje de las ciencias naturales en los estudiantes del décimo año de educación general básica del colegio de bachillerato Primero de Abril de la ciudad de Latacunga provincia de Cotopaxi en el periodo lectivo 2013-2014 - Jácome Borja, Guillermo Patricio (2015)
A research study on ICT impact in the teaching-learning process of Sciences was carried out with tenth graders at ‘Primero de Abril’ High School. According to current research, a methodological guide on the proper use of Information and Communications Technology (ICT) was developed since teachers did not know about the management of technological devices as well as they did not make didactic material based on these technologies. It provoked rote learning, underachievement, little motivation, and disinterest from students. Therefore, this guide will help teachers use in an adequate manner these technologies which are in the educational institution, achieving a meaningful learning. The purpose of this study was to find solutions to problems through a user-friendly guide not only for teachers but also students....